1965
DOI: 10.1254/jjp.15.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Central Depressants on the Evoked Potentials in the Inferior Colliculus Caused by Acoustic Stimuli in the Cat

Abstract: It has been well-known that the electrical activity of the central nervous system is facilitated by relatively lower doses of central depressants.Many reports were presented to support the facilitatory mechanism in the brain of exprimental animals at lower dose levels of barbiturates : lowering of stimulation threshold for the recruiting response by King (1) and' Domino (2), increase in amplitude of the somatosensory evoked poten tial recorded from the internal capsule by King et al. (3), and increase in ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1967
1967
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Brazier (23,24) has shown that the evoked potentials in the visual cortex and Nucleus centre median of thalamus to flash stimulation are inhibited by ether but not by pentobarbital or chloralose. Table 2 summarizes the effects of ether, chloroform, fluothane and nitrous oxide on the cortical and collicular evoked click potentials and unitary discharges in the present experiments comparing with those of pentobarbital sodium, urethane and chlorpromazine reported previously (14)(15)(16)(17). The evoked click potentials in the auditory cortex and in ferior colliculus were depressed by ether inhalation almost uniformly.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Brazier (23,24) has shown that the evoked potentials in the visual cortex and Nucleus centre median of thalamus to flash stimulation are inhibited by ether but not by pentobarbital or chloralose. Table 2 summarizes the effects of ether, chloroform, fluothane and nitrous oxide on the cortical and collicular evoked click potentials and unitary discharges in the present experiments comparing with those of pentobarbital sodium, urethane and chlorpromazine reported previously (14)(15)(16)(17). The evoked click potentials in the auditory cortex and in ferior colliculus were depressed by ether inhalation almost uniformly.…”
Section: Discussionsupporting
confidence: 60%
“…The facilitator), effects of small doses of pentobarbital sodium , chloralose and chlorpro mazine on the cortical evoked click potentials have been reported by Nakai et al (14)(15)(16) in cats. These effects were observed in the supra-thalamic level, and the evoked click potentials in the inferior colliculus were not augmented by these central depressants.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations